Moderation of Personal Relations on Sustainable Competitive Advantages, Customer Relationship Management, and Marketing Performance: Study on small scale business of Leather Products Marketers in East Java - Anggia, Feliks; Salim, Ubud; Sunaryo, Sunaryo; Solimun, Solimun (International Review of Management and Marketing, 2017)
The research approach is quantitative, explanatory. The research analytical unit is a trader of leather industrial products as a small business presentation totaling 65,086 population. The sample of research is the trader who at the same time become the business owner of 398 respondents. The sampling method is the area of proportional random sampling, where the number of samples is determined by using the Slovin formula. Analytical technique using Structural Equation Model with Warp PLS analysis tool. The results show the clarity that personal relationships act as moderators in the relationship of sustainable competitive advantage, customer relationship management with marketing performance. Keywords: Customer Relationship Management, Sustainable Competitive Advantages, Marketing Performance, Personal Relationships JEL Classifications: M12, M31